Natural progression of deep pelvic endometriosis in women who opt for expectant management - Jure Knez; Elisabeth Bean; Simrit Nijjar; Tina Tellum; Prubpreet Chaggar; Davor Jurkovic (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The natural history of endometriosis is poorly understood, and despite numerous studies, the rate of the disease progression and optimal treatment planning in women who are asymptomatic or experience mild symptoms not requiring treatment are unknown. The aim of this study was to assess the behavior of deep endometriosis in women who are managed expectantly without any medical or surgical intervention. Material and methods A retrospective cohort study of women diagnosed with deep endometriosis on transvaginal ultrasound scan at the Department of Gynecology, University College London Hospitals and The Gynecology Ultrasound Centre, London, UK, from April 2007 to April 2022. All women attended for at least two ultrasound scans which were carried out by a single expert ultrasound examiner and at least 6 months apart. The number and position of endometriotic nodules were recorded, and the mean diameter of each nodule was calculated from measurements taken in three orthogonal planes. Results During the study period, 1922 women were found to have moderate or severe deep endometriosis on pelvic ultrasound examination. A total of 135 premenopausal women who were managed expectantly fitted the inclusion criteria. The median number of endometriotic nodules per woman at the initial visit was 2 (range: 0–7), and the median follow‐up time was 666 days (181–2984). In the follow‐up period, 50/135 women (37%, 95% CI: 29–46) developed additional nodules or experienced an increase in nodule size, and 17/135 women (13%, 95% CI: 8–19) had a regression in the number or size of the nodules. In the remaining 68/135 women (50%, 95% CI: 42–59) the disease remained static during the follow‐up. The median change in mean diameter of nodules during the study period per woman was +0.13 mm (−11.67 − +5.83), with an annual growth rate of +0.09 mm/year (−6.65 − +6.45). Conclusions In our study we found evidence of deep endometriosis progression in just over a third of women. In view of this, asymptomatic or mildly symptomatic women diagnosed with deep endometriosis could be reassured that their disease is unlikely to worsen with time.